COMPARISON BETWEEN THE PERFORMANCE OF SQUARE (9) AND SQUARE (144) IN WILLIAM D GANN ANALYSIS-AN ANALYTICAL STUDY OF THE EXCHANGE RATE (GBP/USD) - Prof. Dr. Hashim Jabbar Al-Husseini; Prof. Dr. Haider Abbas Al-Janabi; Muhannad Rashid Sharqi Al-Majidi (Scholars Digest Publishing, 2025)
Technical analysis is one of the main tools that traders and financial analysts rely on to understand price movements in financial markets, and predict future trends. Among the prominent names in the field, the name William D. Gann, who developed a set of analytical tools and methods based on mathematical and temporal concepts, is still of interest and study today. Two of Gann's most prominent tools are the Square of 9 and the Square of 144, two engineering tools believed to reflect the relationship between price and time, helping to identify support and resistance levels, and timing price reversals with high accuracy. This research aims to make an analytical comparison between the performance of Box 9 and Box 144 in the foreign exchange market (Forex), by applying both tools to the popular currency pair GBP/USD, with the aim of testing the accuracy of each in predicting price movement and identifying critical time points. The importance of this study lies in highlighting the practical differences between the two tools, and evaluating their effectiveness in different time contexts, which can contribute to enhancing the efficiency of technical analysis for analysts and traders in the financial markets.